Biomechanical Analysis of Slingshot Grip dan Pull in Traditional Game - Rahesti, Nonik; Irawan, Fajar Awang; Long-Ren, Chuang (Journal of Sport Science and Education, 2024)
Slingshot is a traditional game that has several basic techniques that must be mastered. Some of the basic techniques in the traditional slingshot game have not been fully understood by some players. This study aims to analyze the biomechanical grip and pull of slingshot in traditional games. This quantitative study used a sample consisting of 10 traditional slingshot game players in Semarang Regency. Kinematic data were obtained from the slingshot shooting video analysis using Kinovea software version 0.9.5. The kinematic data consisted of three phases: preparation, release, and followthrough. This study found that the ideal grip is a straight hand position that is parallel to the arm pull until an angle of 90o is formed. Effective and efficient pulling techniques are carried out by pulling and anchoring the rubber in the preparation phase right on the cheekbone as a support point. Hence, the rubber pull is consistent in the same position. Further study needs to be conducted to discuss the analysis of the length of the pulling and shooting accuracy.